PRINSIP BEKERJA KERAS DALAM MENINGKATKAN KESEJAHTERAAN INDIVIDU (STUDI KOMPARASI TERHADAP SISTEM EKONOMI KAPITALISME DAN SISTEM EKONOMI SYARIAH) - Sulis Budiman; Nadya Oktavia; Saifudin; Mila Nadia; Muhammad Fadlum; Ani Faujiah (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
This scientific writing explains how to work hard which can improve individual welfare, through a combination of capitalist theory and sharia,. In this study, we used a research approach in the form of Library Research. Literature study is a study that is used to collect information and data with the help of various materials in the library such as documents, books, magazines, historical stories, etc. (Mardalis: 1999). Keywords: hard work, welfare References Alfat, dkk. 2003. Aqidah Akhlak. Semarang: PT. Toha Putra Ibrahim dan Darsono. 2009. Membangun Akidah dan Akhlak. Solo: PT. Tiga Serangkai Pustaka Mandiri Multahim, dkk. 2007. Pendidikan Agama Islam. Jakarta: Yudistira Tim Penulis. 2009. Materi Inti dan Soal Jawab Pendidikan Agama Islam. Solo : PT. Tiga Serangkai Pustaka Mandiri Muslimin, Muhammad Irwin, and Darwanto Darwanto.